2020
DOI: 10.3390/cancers12113356
|View full text |Cite
|
Sign up to set email alerts
|

Linking Circulating Serum Proteins with Clinical Outcomes in Esophageal Adenocarcinoma—An Emerging Role for Chemokines

Abstract: Esophageal adenocarcinoma (EAC) is an aggressive cancer with poor prognosis and incidence is increasing rapidly in the Western world. Multi-modal treatment has improved survival outcomes but only for a minority of patients. Currently no markers have been identified to predict treatment response. This study investigated the association between clinical outcomes and pre-treatment levels of 54 serum proteins in n = 80 patients with EAC. Low tumor regression grade (TRG), corresponding to a favorable treatment resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…CXCL13 plays a key role in the development of tertiary lymphoid structures through engagement with CXCR5 + follicular helper cells and B cell recruitment, although CD8 + CXCL13 + T cells are observed in many tumors and enriched within exhausted PD-1 high subsets (Thommen et al, 2018), (Workel et al, 2019),(van der Leun et al, 2020). CCL4 attracts innate cells and its serum level is increased in EAC where it correlates with both the degree of lymphocytic in ltrate and superior clinical outcome (Donlon et al, 2020). Important modi cations of the T cell repertoire were seen after chemotherapy with a marked reduction in T regulatory populations together with relative enhancement of effector pools.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL13 plays a key role in the development of tertiary lymphoid structures through engagement with CXCR5 + follicular helper cells and B cell recruitment, although CD8 + CXCL13 + T cells are observed in many tumors and enriched within exhausted PD-1 high subsets (Thommen et al, 2018), (Workel et al, 2019),(van der Leun et al, 2020). CCL4 attracts innate cells and its serum level is increased in EAC where it correlates with both the degree of lymphocytic in ltrate and superior clinical outcome (Donlon et al, 2020). Important modi cations of the T cell repertoire were seen after chemotherapy with a marked reduction in T regulatory populations together with relative enhancement of effector pools.…”
Section: Discussionmentioning
confidence: 99%
“…Known functions of bFGF include the enhancement of tumour cell proliferation, survival, motility, and wound healing [40]. Previous studies in oesophageal cancer demonstrated that bFGF overexpression is associated with a risk of tumour recurrence and reduced OS post-surgical resection, suggesting bFGF may play an important role in TME remodelling and enhancement of tumour progression [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that when tumor cells overexpressing HMGB1 co-cultured with B cells, the proliferating B cells can be induced to express VEGF and then elevate angiogenesis ( 121 ). A significant decrease in VEGF-C has been found in high tumor lymphocytic infiltration ( 122 ). It is reported that low expression of CD80 can be associated with VEGF overexpression.…”
Section: The Role Of Cellular Communication In Esophageal Squamous Ce...mentioning
confidence: 99%